1999
DOI: 10.1126/science.283.5399.205
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene Extinction of Genyornis newtoni : Human Impact on Australian Megafauna

Abstract: More than 85 percent of Australian terrestrial genera with a body mass exceeding 44 kilograms became extinct in the Late Pleistocene. Although most were marsupials, the list includes the large, flightless mihirung Genyornis newtoni. More than 700 dates onGenyornis eggshells from three different climate regions document the continuous presence of Genyornis from more than 100,000 years ago until their sudden disappearance 50,000 years ago, about the same time that humans arrived in Australia. Simultaneous extinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
213
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(222 citation statements)
references
References 18 publications
6
213
0
1
Order By: Relevance
“…Under the Allen and coworkers interpretation, this would imply that modern humans arrived in Australia at the same time as both modern humans and extinct Neanderthal arrived in Europe, possibly about 50 ka. Similarly, the distributions in Figure 4B would imply that modern Australians, who were certainly eating the extant fish, shellfish, and emu, could also have been eating the extinct Genyornis (n=22, Miller et al 1999) over this time range.…”
Section: Discussionmentioning
confidence: 94%
“…Under the Allen and coworkers interpretation, this would imply that modern humans arrived in Australia at the same time as both modern humans and extinct Neanderthal arrived in Europe, possibly about 50 ka. Similarly, the distributions in Figure 4B would imply that modern Australians, who were certainly eating the extant fish, shellfish, and emu, could also have been eating the extinct Genyornis (n=22, Miller et al 1999) over this time range.…”
Section: Discussionmentioning
confidence: 94%
“…As discussed above, the AAR technique has the limitation that less racemisation occurs within glacial periods, causing ratios to overlap from successive interglacials (e.g. Miller et al, 1999;McCarroll, 2002;Penkman et al, 2008b, in press). Whilst this overlap is less pronounced when analysing calcitic opercula, it is still necessary to also take into account palaeoenvironmental and biostratigraphic evidence.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of the protein breakdown reactions means that increased degradation occurs during warm stages and there is a slowing in the rates of degradation in cold stages (e.g. see Figure 2 in Miller et al, 1999). As little decomposition occurs in cold stages, and there is a degree of natural variability in biological samples, it can be difficult to discriminate the end of one warm stage from the beginning of the next (Penkman et al, 2008b) and the separation between the end of MIS 11 and the beginning of MIS 9 is particularly difficult using the amino acids presented here (Ashton et al, 2008;Roe et al, 2009).…”
Section: Aar Valuesmentioning
confidence: 99%
“…In addition, at some point during the Quaternary megafauna including Diprotodon, Genyomis and other giant marsupials became extinct. Miller et al (7) suggested that this extinction might be related to the arrival of hominins. Alternatively extinction might have resulted from environmental changes.…”
Section: Marsupial Teethmentioning
confidence: 99%
“…Ages can, therefore, be cross-calibrated both with 14 C and with ^Ar/^Ar results. Most archaeological applications have used enamel from teeth of large placental mammals such as bovids and equids, in part because teeth, being the hardest tissues in the body, are often preserved (7). There are many environments and time periods where placental mammals are rare or non-existent.…”
mentioning
confidence: 99%